PSII-25 The effect of the organic acid on the bulls' sperm quality. (5th December 2019) - Anipchenko, Polina; Plemyashov, Kirill; Nikitin, Georgiy; Nikitina, Anastasia; Shabunin, Sergey
Abstract: Carnitine is actively used in medicine in the treatment of male infertility. L-carnitine is an organic acid that normalizes the balance of oxidative and antioxidant processes. Bulls (n = 15) with low sperm quality (low sperm activity) were selected. The bulls were injected intramuscularly L-carnitine solution (NaturVet, Australia) at the rate of 1 ml per 30 kg of animal body weight twice a week for one month. A macroscopic assessment of the ejaculate was carried out, the activity of the spermatozoa in the freshly obtained ejaculate, the concentration, the activity of the spermatozoa after thawing the sperm samples was evaluated.Investigated samples obtained from bulls one month before the start of L-carnitine using, during the period of the experiment and during one month after the end of the experiment.The minimum value of sperm activity in the period prior to the use of L-carnitine was 2 points. The average activity of bull semen is 2.7 points. Research results showed that the average score of sperm activity increased to 7.2 points. The maximum value of sperm activity is 8 points.The volume in the period prior to the injection of L-carnitine was 1.9 ml, while the drug was in use - 3.4 ml. The sperm production rate increased by 44%.The average value of sperm concentration in the ejaculate of bulls when using L- carnitine was 0.9 billion / ml. This indicator increased by 11% compared to this indicator in the period before using of the drug (0.8 billion / ml). Thus, based on the data obtained, it can be noted that using the injection form of the L-carnitine solution has a positive effect on the quality of sperm obtained from bulls.